Integrated treatment of depression and moderate to severe alcohol use disorder in women shows promise in routine alcohol use disorder care – a pilot study - Persson, Anna; Finn, Daniel Wallhed; Broberg, Alice; Westerberg, Amanda; Magnusson, Åsa; Molander, Olof (Frontiers in Psychiatry, 2025)
IntroductionMajor depression and alcohol use disorder affect millions of individuals worldwide and cause significant disability. They often occur together, and their co-occurrence is associated with more negative outcomes than each disorder on its own. Yet, there is a lack of knowledge on how to best treat co-occurring depression and alcohol use disorder. A pilot study was conducted to investigate the feasibility, credibility, patient satisfaction, preliminary effect, and potential negative effects of an integrated treatment for depression and alcohol use disorder, which has shown promising results in an earlier pilot trial.MethodsThe study was conducted at an outpatient unit in Stockholm, Sweden. Women (n=7) with current depression and alcohol use disorder were offered integrated group treatment that included evidence-based treatment for depression and alcohol use disorder. Criteria for feasibility were based on an earlier study, treatment credibility was measured using the Credibility/Expectancy Questionnaire and patient satisfaction with the Client Satisfaction Questionnaire.ResultsFeasibility, credibility, and patient satisfaction were high. Depression symptom severity and alcohol consumption decreased from baseline to follow up. Negative effects were reported in terms of increased adverse emotional experiences.DiscussionThe investigated integrated treatment for co-occurring depression and alcohol use disorder continues to show promise. Randomized clinical trials are needed to evaluate its effectiveness.